A product design methodology and a global optimisation model for QFD planning process. (1st January 2014) - Cherif, Mohamed Sadok; Aouni, Belaïd; Chabchoub, Habib
The aim of this paper is to propose a product design methodology (PDM) and a combined benchmarking and goal programming (GP) model that attempt to enhance the effectiveness and efficiency of quality function deployment (QFD) as a means to introduce explicitly the customer's preferences into the design and the production processes. The PDM contributes to the strategic guidance and provides clear direction for designers in the early stage of product development. The GP model helps in making key tradeoffs between both satisfactions of customer and designers during the QFD planning process. Focusing on determining a set of engineering characteristics (ECs) that most effectively meet customer requirements (CRs), our explicit model takes into consideration the customer's preferences(best customer perceptions of CRs on the target market), the designers' preferences (product design strategies of the company, market competition, financial factors and other design restrictions), and the uncertainty of data of the decision-making environment. A numerical example is used to illustrate the proposed model.